2016
DOI: 10.7205/milmed-d-14-00333
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Transcendental Meditation on Psychotropic Medication Use Among Active Duty Military Service Members With Anxiety and PTSD

Abstract: The purpose of the study was to determine whether the regular practice of Transcendental Meditation (TM) decreased the need for psychotropic medications required for anxiety and post-traumatic stress disorder (PTSD) management and increased psychological wellbeing. The sample included 74 military Service Members with documented PTSD or anxiety disorder not otherwise specified (ADNOS), 37 that practiced TM and 37 that did not. At 1 month, 83.7% of the TM group stabilized, decreased, or ceased medications and 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 25 publications
1
18
0
Order By: Relevance
“…25 The results of this study are similar to those of earlier studies that have evaluated the effects of the TM program on PTSD. [6][7][8][9][10][11] In addition, more than 350 scientific studies published in over 160 peer-reviewed scientific journals have documented the benefits of TM practice for mind, body, and behavior. 20 When considering all of the research on the impact of the TM technique in reducing psychological and physiological stress, the convergence of evidence suggests that TM practice may offer a promising adjunct or alternative method for treating PTSD that may be more acceptable to many of those with PTSD than current approaches.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 The results of this study are similar to those of earlier studies that have evaluated the effects of the TM program on PTSD. [6][7][8][9][10][11] In addition, more than 350 scientific studies published in over 160 peer-reviewed scientific journals have documented the benefits of TM practice for mind, body, and behavior. 20 When considering all of the research on the impact of the TM technique in reducing psychological and physiological stress, the convergence of evidence suggests that TM practice may offer a promising adjunct or alternative method for treating PTSD that may be more acceptable to many of those with PTSD than current approaches.…”
Section: Discussionmentioning
confidence: 99%
“…10 Barnes et al found a reduction in psychotropic medication use among active duty military soldiers with anxiety disorder and PTSD, which suggests their PTSD symptoms had decreased. 11 The previously published research on the direct impact of TM practice on veterans' PTSD symptoms consists of pilot studies. This study seeks to expand this area of research by evaluating a larger sample of veterans than earlier studies.…”
Section: Introductionmentioning
confidence: 99%
“…This behavior may arise due to alterations in self-perception [75]. Healing deep rest, counteracting the stress response, experienced during Transcendental Meditation is being used to treat PTSD in active duty Service Members [76]. Cognitive Behavioral Therapy has been shown to be effective in treating PTSD by assisting patients in identifying traumatic memories and thoughts, confronting these, and replacing them with more comforting thoughts [77].…”
Section: Ptsd Depression and Deliberate Self-harmmentioning
confidence: 99%
“…Stress management via meditation has shown to be effective in treating anxiety a post traumatic stress [101][102][103][104][105]. Visits to primary care providers related to stress account for 60-80% of visits, yet few stress-related visits are accompanied by stress management counseling [106].…”
Section: Clinical Applications Arising From Our Understanding Of the mentioning
confidence: 99%